Stress-induced α″ martensite and its variant selection in a metastable β titanium alloy under an uniaxial compression - Ruifeng Dong; Yuxin Tan; Hua Hou; Guangxiao Ren; Nan Wang; Yuhong Zhao (Journal of Materials Research and Technology, 2024)
The phase transformation of β to stress-induced α″ martensitic progresses in a displacive mode. The associated transformation strain induced by β to α″ martensitic has an important influence on the resultant microstructure. In this work, the stress-induced α″ martensitic transformation and its variant selection behavior were investigated in a metastable β titanium alloy under an uniaxial compression. The lattice distortion of β to α″ martensitic indicated that the shear strain on {112} planes and in <11 1‾ > directions mainly dominate the transformation. During the slight compression, only a limited number of α″ variants were selectively formed within β grains, i.e. the occurrence of variant selection of α″ martensite. The results showed that the selected variants of α″ martensite are preferential those with high Schmid Factors on their corresponding {112}/<11 1‾ > shear systems.